Diversity of Migratory Fish in Floodplain Rivers in Sumatra: A Review Article - Rahma Yulita; Roza Elvyra; Tetty Marta Linda (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2026)
The floodplain areas in Sumatra play a crucial ecological and sociological role for aquatic life and surrounding communities. However, this ecosystem faces serious threats from anthropogenic activities such as land conversion into palm oil plantations, infrastructure development (dams), and industrial pollution. This article conducts a literature review regarding the diversity of migratory fish in various floodplain rivers in Sumatra. The review results indicate that the fish community in these areas is dominated by the potamodromous fish group. The Cyprinidae family was found to have the highest number of species. Conservation data show the presence of species with concerning statuses, including an Extinct (EX) status for Chitala lopis and Endangered (EN) for Pangasianodon hypophthalmus, which correlates with massive habitat degradation. This information is expected to support conservation efforts for sensitive species and maintain connectivity between river ecosystems.